Pengaruh Rating Produk Dan Review Produk Terhadap Minat Beli Ditiktok Shop Dengan Kepercayaan Konsumen Sebagai Variabel Intervening : Studi Kasus Mahasiswa Semester 8 STIE Bina Karya Tebing Tinggi - Suwadi, Suwadi; Filza, Nadia Ananda; Fazillahi, Raihan Anggi (STIE Bina Karya, 2025)
This research aims to determine the influence of Product Ratings and Product Reviews on Purchase Interest in Ditiktok Shop with Consumer Trust as an Intervening Variable (Case Study of Semester 8 Students of Bina Karya Tebing Tinggi). The research method used is a quantitative method using SPSS assistance collected from the results of distribution questionnaire totaling 73 respondents. The analytical method used for Measurement Evaluation (Outer Model) is Validity Test and Reliability Test. Then the Structural Model (Inner Model) method is the Determination Coefficient (R2), Goodness of Fit Model (GoF), T-Statistic Test and Indirect Effect Test. The analysis tool in this research uses SPSS Version 25. The results of this research are that product reviews influence consumer confidence, product reviews influence consumer confidence, product ratings influence purchasing interest, product reviews influence purchasing interest, consumer trust influences purchasing interest. , Product ratings can mediate the influence of purchasing interest on consumer confidence and product reviews do not mediate the influence of purchasing interest on consumer confidence.